Immunoscintigraphy in Medullary Thyroid Cancer Using an 123I- or 111ln-Labelled Monoclonal Anti-CEA Antibody Fragment - Reiners, Chr.; Eilles, Chr.; Spiegel, W.; Becker, W.; Börner, W. (Nuklearmedizin - NuclearMedicine, 1986)
The monoclonal anti-CEA F(ab’)2 fragment MAb BW 431/31, labelled with 123I or111 In, was used for immunoscintigraphy (IS) in 9 patients with medullary cancer of the thyroid (CCC). The results of 11 studies lead to the following conclusions: 1) When using radioiodine as a label for MAb in IS, potassium iodide is absolutely necessary to block the thyroid which is of special importance in patients with thyroid cancer; 2) Preinjection of “cold” MAb reduces the relatively high unspecific uptake (especially in bone marrow) of MAb BW 431/31, which is of special importance for the antibody labelled with 111 In; 3) IS with MAb BW 413/31 in patients with CCC and elevated serum CEA is positive only in cases with large secondaries; and 4) In patients with CCC and several manifestations of secondaries, only a single (large) metastasis may be apparent.Das monoklonale anti-CEA F(ab’)2-Fragment MAb BW 431/31, markiert mit 123J oder 111ln, wurde bei 9 Patienten mit medullärem Schilddrüsen- Karzinom (CCC) zur Immunszintigraphie (IS) verwendet. Die Ergebnisse von 11 immunszintigraphischen Untersuchungen führten zu folgenden Schlußfolgerungen: 1. Bei der IS mit radiojodmarkiertem MAb muß die Schilddrüse unbedingt mit Kaliumjodid statt mit Perchlorat oder Schilddrüsenhormonen blockiert werden. Diese generelle Forderung ist von besonderer Bedeutung für die Untersuchung von Patienten mit Schilddrüsenkarzinom; 2. Der relativ hohe unspezifische Uptake des MAb BW 431/31 (vor allem ins Knochenmark) kann durch Vorinjektion von unmarkiertem Antikörper reduziert werden. Dies erweist sich insbesondere bei dem 111In- markierten MAb als vorteilhaft; 3. Die IS mit dem MAb BW 431/31 ergibt bei Patienten mit CCC und erhöhtem Serum-CEA nur im Falle sehr großer Metastasen eindeutig positive Befunde; und 4. Bei Patienten mit CCC und Metastasen in mehreren Lokalisationen ist häufig nur eine (große) Manifestation immunszintigraphisch positiv.